Clinicopathology of Domestic Pigeon Infected with Haemoproteus columbae: A Case Report - Suandhika, Putu; Wahidah, Edwin Habibatul; Sewoyo, Palagan Senopati (Indonesia Medicus Veterinus, 2025)
INTRODUCTION: Haemoproteosis, or pseudomalaria in pigeons, is a disease caused by the protozoan Haemoproteus columbae . This disease is prevalent in subtropical and temperate regions. OBJECTIVE: The present case report delineates the occurrence of haemoproteosis in a pigeon, with a primary emphasis on describing the clinical condition, gross and histopathological alterations within the trachea, kidneys, and pancreas. METHODS: A male pigeon with blackish-gray feathers was purchased from Splendid Market, Malang, Indonesia. Physical examination was performed to identify any clinical abnormalities that might not have been noticed by the seller. Inspection showed the presence of ectoparasites across the pigeon’s feathers with no external wound. RESULTS: The ectoparasite Columbicola columbae was identified in the plumage through microscopic analysis, although the pigeon displayed no discernible clinical symptoms. Blood samples were obtained from the afflicted pigeon, and subsequent blood smear preparations were subject to Giemsa staining and microscopic observation. Notably, the microscopic examination revealed the presence of the parasite Haemoproteus columbae . Subsequently, the affected animal was euthanized through decapitation, and necropsy was conducted. Gross pathology examination revealed signs of inflammation in the trachea, renal punctate lesions, and hemorrhage and enlargement in the pancreas. Histopathological findings indicated necrotizing tracheitis, necrotizing interstitial nephritis, and pancreatitis. CONCLUSIONS: Based on these findings, the pigeon was diagnosed with haemoproteosis.